Foreign Direct Investments in the German Stock Market from China and the Gulf States - Ann-Kristin Achleitner; Dmitry Bazhutov; André Betzer; Henry Keppler (Credit and Capital Markets – Kredit und Kapital, 2021)
We document empirical evidence that the investment patterns of the two most relevant investor groups from regions with hierarchical structures in the German stock market, namely China (including Hong Kong) and the Gulf Cooperation Council, differ substantially. Chinese investors buy large shares in relatively small, but not necessarily young, companies. Since their objective is often to gain control, they appear to pay higher premiums when acquiring large equity stakes. Investors from the Gulf states purchase smaller shareholdings in notably larger, older, and more international companies. They seem to seek long-term benefits rather than short-term profits. Our findings are mainly attributable to industrial policies pursued by Chinese and Gulf investors, which mirror the different political and economic goals in these two regions.
Keywords: G11; G18; G34; G38; 330; Foreign Direct Investments; China; Gulf States; Corporate Governance; Event Study